Les médiateurs sociaux : limites et enjeux d'un dispositif - Henri Vieille-Grosjean; Rachel Solomon Tsehay (Sociétés et Jeunesses en Difficulté)
Following a study aimed at measuring the limits and challenges of the social mediation system, the authors put forward an examination in this article of the mutual expectations of the social mediator and its employer, the urban community. This sociological study is comprehensive: it uses the method of the individual interview and focus group. The analysis of the results is supported by contributions from Boltanski and Thévenot in order to compare the reference “worlds” of both types of actor. It is supplemented by the analysis of notions of “system” (Foucault) and “professionalisation” (Hainaux et al., Bartoli). The authors try to understand the extent to which the actors understand involvement in mediation.